NEW APPROACHES TO EMPLOYEE MOTIVATION IN THE LOGISTICS SECTOR - KOSTETSKYI, Volodymyr; DUDKIN, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In today’s extremely challenging environment, the logistics industry is going through a tough time. To improve the performance of enterprises, it is necessary to motivate employees properly. Especially employees of commercial, sales, or marketing departments, on whom the company’s performance directly depends. Nowadays, paying a rate and percentage for employees is no longer enough. Financial motivation no longer works as well as it used to, as employees can easily change the workplace or even their field of activity. That is why the question of establishing new approaches to staff motivation has arisen. The article covers the issue of creating a corporate culture in which employees can work comfortably and efficiently. In this case, the article considers the aspect of strategic motivation by communicating to the employees the opportunities and benefits that a person can achieve over a certain period in the successful performance of their functional and job responsibilities. Employees also need to see and understand what the company will look like in a few years and see themselves in the company in a few years. In other words, an important approach to motivation is to involve employees in long-term projects and company goals. The report also analyses the crucial elements of motivation for employees: mobility, convenience, personal safety, and family safety. It means the possibility of a remote workplace, or a combination of office work and work from home or a coworking center. The article analyses the situation in the logistics labor market from December 2021 to December 2024. The focus is on changes in the state’s situation state in the field of logistics in these periods, as well as on the motivation system in the relevant periods. Changes in the salaries of employees in the logistics sector are considered. The periods and corresponding motivation systems that successfully proved themselves in the appropriate periods are considered. The main approaches to the effective motivation of logistics personnel in the present and future are highlighted.